Exploring the relationship between tourism development impacts on community quality of life and their support for further development: a case of Malaysia homestay experience programme / Noriman Rojulai - Rojulai, Noriman (2021)
Perception of local communities on the impact of tourism on the quality of life is essential in influencing their participation in tourism. When more benefits the local communities gained from tourism, the more the support they will provide. Past research has shown that the concept of responsible tourism is one of the alternatives to minimise the negative impact on tourism and increase the long-term benefit to the local communities. The objective of this study is to investigate the correlation between the perceived impact of Malaysia Homestay Experience Programme (MHEP) development, responsible tourism practice, the quality of life and support for further MHEP development. The study applied the Social Exchange Theory (SET) as an underpinning theory to explain the relationship between the variables. The design of the study is quantitative and cross-sectional. A total of 385 responses were analysed and Partial Least Square Structural Equation Modelling (PLS-SEM) was used in hypotheses testing. This study affirms that quality of life partially mediates the relationship between the perceived impact of MHEP (economic and culture) and support for further tourism development. The findings have shown that quality of life is not the sole factors affecting the support of the local communities toward the programme. This study also reports that responsible tourism practice influences the relationship between the perceived impact of MHEP (economic and culture) and quality of life. The results of the analysis indicated that the local communities residing in the MHEP, are most likely concerned on the economic and cultural benefit. In the bigger perspective, these findings may provide an important guide and direction to the relevant authorities such as the Ministry of Tourism, Arts and Culture (MOTAC) to improvise the existing MHEP.